2016
DOI: 10.1371/journal.pone.0167125
|View full text |Cite
|
Sign up to set email alerts
|

Dose Dependent Dual Effect of Baicalin and Herb Huang Qin Extract on Angiogenesis

Abstract: Huang Qin (root of Scutellaria baicalensis) is a widely used herb in different countries for adjuvant therapy of inflammation, diabetes, hypertension, different kinds of cancer and virus related diseases. Baicalin is the main flavonoid in this herb and has been extensively studied for 30 years. The angiogenic effect of herb Huang Qin extract and baicalin was found 13 years ago, however, the results were controversial with pro-angiogenic effect in some studies and anti-angiogenic effect in others. In this paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 68 publications
0
14
0
Order By: Relevance
“…A recent study reported the angiogenic properties of baicalin by using chick embryo chorioallantoic membrane [126]. The aqueous extract of baicalin showed both inhibitory and angiogenic activities while the baicalein showed only anti-proliferative property.…”
Section: Scutellaria Baicalensismentioning
confidence: 99%
“…A recent study reported the angiogenic properties of baicalin by using chick embryo chorioallantoic membrane [126]. The aqueous extract of baicalin showed both inhibitory and angiogenic activities while the baicalein showed only anti-proliferative property.…”
Section: Scutellaria Baicalensismentioning
confidence: 99%
“…Scutellaria baicalensis Georgi (known as huang qin) is a traditional Chinese herb, that has been shown to exhibit antioxidant, anti-inflammatory, anti-bacterial and anti-viral, antidiabetic and anti-dyslipidemic activities [9,10]. Baicalin (BAL) is one of the most potent flavonoids isolated from the radix of Scutellaria baicalensis [11,12]. Anti-inflammatory activity is a primary biological potential of BAL in a variety of diseases and disorders [13], including rheumatoid arthritis, obesity, type 2 diabetes, respiratory diseases, inflammatory bowel diseases, cardiovascular diseases, autoimmune encephalomyelitis, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Flavonoids have been reported to modulate several angiogenic factors and cascades in either a proangiogenic or an antiangiogenic manner which is postulated to be dose dependent [ 2 , 148 ]. A good illustration of this dual effect is demonstrated by the flavone baicalin; low doses were reported to stimulate angiogenesis [ 152 ] whilst high doses showed an inhibitory effect [ 153 ].…”
Section: Discussionmentioning
confidence: 99%